Exploring the Role of Leadership Style and Organizational Culture in Shaping Employee Performance - Yohanes Gulo; Rifki Suwaji (PT Mattawang Mediatama Solution, 2025)
Leadership style and organizational culture are considered two significant factors influencing employee performance at PT Aneka Mode Indonesia. This study aims to examine the influence of leadership style and organizational culture on employee performance within the company. The research employed a quantitative approach, conducted on a group of employees selected using a probabilistic method. Data were collected using a closed-ended questionnaire with a five-point Likert scale ranging from strong disagreement to strong agreement. The data analysis involved descriptive statistics and inferential analysis, utilizing both simple and multiple regression techniques. Hypothesis testing was carried out using t-tests and F-tests. The findings indicate that leadership style positively influences employee performance. Similarly, organizational culture also has a positive effect on employee performance. Furthermore, when considered simultaneously, both leadership style and organizational culture have a joint positive influence on employee performance. These findings suggest the importance of improving leadership practices and fostering a strong organizational culture as strategic efforts to enhance employee performance.